Helping deprived farmers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
The Farmers Development Union is an association of farmers in development and promotes the hopes, activities and determination of the rural poor and the marginalized with the aim of achieving development which is truly sustainable, culturally...